Customer satisfaction towards service quality at Mahkota Medical Centre / Siti Hajjar Mohd Ayub - Mohd Ayub, Siti Hajjar (2015)
This research was conducted to carry out a study entitled “Customer Satisfaction towards the Service Quality at Mahkota Medical Centre”. Compared to year 2012 complaints received by Mahkota Medical Centre for year 2013 had increase by 15%. The purpose of this study is to determine the level of customer satisfaction in Mahkota Medical Centre. Besides that, this purpose is to determine the relationship between the service quality and customer satisfaction. Finally, this research has been conducted to determine the dimension of service quality that the most contribute to customer satisfaction of Mahkota Medical Centre. In order to completing this research, the hypothesis was been constructed and focused on the objective to determine whether there has significant relationship between those tangibility, reliability, responsiveness, assurance, empathy between customer satisfactions. For this study, customers in Mahkota Medical Centre were chosen as respondents. A questionnaire had been distributed to those who involved which are 217 participants. The data was obtained from primary data by using questionnaires. All data collected through the questionnaires were analyzed systematically by Statistical Package for Social Science (SPSS). The results show the dimension of service quality which are tangibility, reliability, responsiveness, assurance and empathy have relationship toward customer satisfaction. From the findings, most of the customers were satisfied with the service quality provide by Mahkota Medical Centre. Recommendations toward industry and future research have been identified to help Mahkota Medical Centre and future research to increase customer satisfaction towards Mahkota Medical Centre.